High-Protein Concentrated Pro-Yogurt (Pro-WPI) Enriched With Whey Protein Isolate Improved Athletic Anemia and Performance in a Placebo-Controlled Study - Gomaa, Mohamed A. E.; Allam, Marwa G.; Haridi, Abdallah A. I. M.; Eliwa, Alaa-Eldin M.; Darwish, Amira M. G. (Frontiers in Nutrition, 2022)
Upcoming developments are attracting attention to both high-protein and probiotics supplementation for the sports community to promote good health and exercise performance. This study aimed to the production of high-protein concentrated pro-yoghurt (PRO-WPI) enriched with 10% and 20% whey protein isolate (WPI) and investigation of the response of daily consumption on anthropometric, hematology parameters and athletic performance in parallel with safety considerations assessment. Twenty four athletes (19.6± 1.45 years; 175.96± 5.24 cm; 73.16± 8.65 kg) were participated in a randomized placebo control study. They had consumed Pro-WPI products with 10% (T1) and 20 % (T2) WPI for treatments G1 (Pro-WPI30) and G2 (Pro-WPI60) respectively for 3 times per day/ 5 days per week/ 9 weeks. Pro-WPI products’ taste was sour and cheesy, while mouthfeel was described as soft and thick due to the increased protein content of T1, T2 (14.15%, 22.58 %). Athletes’ hemoglobin increased significantly from baseline of (12.69 g/dl) to (16, 16.66 g/dl) in G1 and G2. Furthermore, the athletic performance was enhanced in vertical jump, long jump, sprinting velocity, half squats and pushups to reach (58.75 cm, 255 cm, 3.5 m/s, 218.75 counts and 85 counts) in G2. The healthy gut microbiome (probiotics) in parallel with increased iron bioavailability by mineral binding (whey bioactive peptides), influenced the iron status and can represent a healthy practice to enhance athletic anemia and performance. On the other hand, urinary albumin exceeded the border of the reference range (<30 mg/g) to reach (38.25, 44.13 mg/g) in G1 and G2, while the urine pH was in normal range (4.5-8). Increased urinary albumin might be due to the high rates of protein metabolism that follow high protein intake. This study provided preliminary information of metabolic responses to high protein concentrated yoghurt intake in athletes who engaged in a daily exercise. Further studies are needed to determine the recommended intensity of 10% and 20 % Pro-WPI products consumption to achieve its benefits avoiding implications on kidney function.